Dietary exposures to metals in relation to chronic kidney disease of unknown cause (CKDu) in Sri Lanka - Nyachoti, S.; Godebo, T. R.; Okwori, O. F.; Jeuland, M. A.; Manthrithilake, Herath (Springer, 2022)
Exposure to metals has been hypothesized as possible cause of chronic kidney disease of unknown cause (CKDu) in Sri Lanka; however, evidence is inconclusive. We measured the concentrations of nephrotoxic metals (As, Pb, and Cd), as well as Se in rice (a staple grain in Sri Lanka) and other grains consumed in CKDu endemic and non-endemic regions using Inductively Coupled Mass Spectrometry (ICP-MS). Our results showed comparable mean concentrations (in µg/kg) of 24.5±18, 7.3±6.4, and 14.2±15 for As, Pb, and Cd, respectively, in rice from endemic regions and 17.7±4.7, 12.7±6.8, and 17.8±16 in rice from non-endemic regions. Selenium concentrations (in mg/kg) were 0.05±0.02 in rice cultivated in both endemic and non-endemic regions. Arsenic and Cd concentrations were significantly higher in rice compared to other grains, which themselves had higher Se than rice. All samples were below the Codex standards established for Cd (400 µg/kg for rice; 100 µg/kg for cereal grains), Pb (200 µg/kg) and inorganic As (200 µg/kg) for white rice. Our findings show that dietary exposure to low levels of As, Pb, Cd, and inadequate Se in staple grains cannot be clearly linked to CKDu, suggesting that the disease could be multifactorial. Additional research is needed to determine the contribution of other risk factors such as lifestyle habits and heat stress to plan preventive strategies for reducing CKDu health cases in Sri Lanka.